Potentially toxic metals in the tropical mangrove non-salt secreting Rhizophora apiculata: A field-based biomonitoring study and phytoremediation potentials - Chee, Kong Yap; Al-Mutairi, Khalid Awadh (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The present study evaluated the potentials of phytoremediation and the biomonitoring of potentially toxic metals (PTMs) (Zn, Ni, Fe, Pb, and Cu) in the mangrove leaves of Rhizophora apiculata from the tropical mangrove ecosystem in the Sepang Besar River and Lukut River, Peninsular Malaysia. Overall, the present studies concluded that (a) the levels of essential Fe, Cu, and Zn in lamina are significantly (p < 0.05) higher than in MP, (b) the levels of Pb and Ni in MP are significantly (p < 0.05) higher than in lamina, (c) the lamina has better potential as a phytoremediator of Cu, Zn, and Fe, while MP is a better potential phytoremediator of Pb and Ni, (d) lamina is a potential biomonitoring agent of potentially toxic metals based on better correlation coefficients with the surface sedimentary geochemical fractions, and (e) metal uptake in the mangrove leaves and comparative levels of metals is low with reported studies. Specifically, based on bioconcentration factors (BCF), their most obtained values were considered low (<1), suggesting that R. apiculata can be considered as a low-efficiency plant for the bioaccumulation of PTM. However, the present findings also suggested that R. apiculata may be classified as a potential phytoremediator for Zn, Cu, Pb, and Ni in the leaves, as indicated by higher metal accumulation in the MP, with BCFEFLE values > 1.0; BCFAR > 1.0 for Cu, Pb, and Ni. The mangrove leaves are potential biomonitors of PTMs since positive correlations of PTMs were found between the leaves and their habitat surface sediments. Having been identified as a potential phytoremediator and biomonitor of PTMs, the present study emphasized the possibility of establishing a framework for managing the coastal aquatic ecosystems along the mangrove ecosystems of Sepang and Lukut.